(untitled) (Academicia Globe: Inderscience Research, 2022)
In the article is interpreted the issues of innovative approach, modernization of the educational system, the essence of Educational Technology, Principles, criteria for the educational technology implementation, technological development of the educational process, design of the educational process, orientation of educational technology towards students’ activities.